Coordinated Regional-District Operation of Integrated Energy Systems for Resilience Enhancement in Natural Disasters - Yan, Mingyu; He, Yubin; Shahidehpour, Mohammad; Ai, Xiaomeng; Li, Zhiyi; Wen, Jinyu (IEEE transactions on smart grid, 2019)
This paper proposes a coordinated regional-district operation of integrated energy system (IES) for enhancing resilience in extreme conditions. A bi-directional flow model is established for regional-district IES with the utilization of power-to-gas technologies which shows how regional and district IES can jointly enhance the IES resilience. The regional IES co-optimizes power grid and natural gas networks, while the district IES coordinates the energy conversion and storage facilities. The district IES is modeled as an energy hub which supplies electricity to the regional IES. A tri-level two-stage robust model is established to accommodate random outages caused by natural disasters in both natural gas and electricity generation and delivery systems. A two-level algorithm utilizing Benders decomposition and column-and-constraint generation algorithms is proposed to solve the robust IES problem. Numerical results tested on a 6-bus electrical-6-node natural gas system and a modified IEEE RTS-79 40-node natural gas system show the effectiveness of the proposed model and solution technique for enhancing the IES resilience.